Physical properties of FG HAP-F75 fabricated by powder metallurgy - Noorazimah, Mohd Ab Llah; Shamsul Baharin, Jamaludin, Prof. Dr.; Nur Hidayah, Ahmad Zaidi (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.